Electroencephalogram Spectrum in Children with Neurological Disorders an Experience of Tertiary Care Hospital - Shazia Kulsoom, Erum Majid, Shazia Soomro, Sanam Bano, Taj Muhammad, Zubair Khoso (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Objective: For evaluation of brain function in medical and psychiatric disorders one of the important investigative tool is Electroencephalogram (EEG) . There are limited studies overall related to use of EEG however in pediatric population there is scarcity of standard data related to topic Therefore, the objective of this study is to evaluate the prevalence of abnormal EEG and related neurological disorders in children. Methods: A retrospective analysis of 664 EEG was done. One year record from 1st October 2020 to 30th September 2021 was reviewed .EEG request forms and reports were retrieved from neurophysiology lab data of the institute. A structured Pre-designed questionnaire used for collection of data information collected include demographics , history and conclusion were noted on the proforma. Results: Total of 664 childrens has complete Electroencephalogram and bio-demographic records. The Mean age was 5.5 ± 4 SD at presentation was . Males 375( 63.5%) and 290(43.6%) were females. Males to female ratio was. Among total ,375 (56%) EEG were normal, while 408(61.4%) patients had history of seizure. whereas 256 ( 38.5%) had provisional diagnosis other than seizure and 61 (29%) of them abnormal EEG tracing. Conclusion: In developing countries EEG yet plays an essential role in the evaluation of neurological disorder particularly epilepsy. Therefore efforts needed to establish fully equipped neurophysiology facilities at least in tertiary care pediatric hospitals for early diagnosis and optimum prognosis. Keywords: Electroencephalogram, Neurological Disorders, patterns